1991
DOI: 10.1111/j.1365-2044.1991.tb09595.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high and low doses of suxamethonium

Abstract: SummaryIn a double-blind study, 67 young adult patients undergoing anaesthesia for dental extractions were allocated at random to receive either 0.5 mglkg or 1.5 rnglkg suxamethonium. A greater increase in arterial pressure was seen following induction in the 1.5 mgikg group, aIthough overall intubating conditions were similar in the two groups. Suxamethonium-associated muscle pains were signijfcantly more common in the group which received the larger dose (p<0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
2
22
1
Order By: Relevance
“…[41012] Stewart et al . [11] reported that 26 (96%) of 27 patients receiving 1.5 mg/ kg succinylcholine and 30 (94%) of 32 patients receiving 0.5 mg/kg had acceptable intubating conditions. However, in patients with a full stomach or in those with raised intracranial pressure, excellent intubating conditions are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[41012] Stewart et al . [11] reported that 26 (96%) of 27 patients receiving 1.5 mg/ kg succinylcholine and 30 (94%) of 32 patients receiving 0.5 mg/kg had acceptable intubating conditions. However, in patients with a full stomach or in those with raised intracranial pressure, excellent intubating conditions are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Stewart et al . [11] reported that, after induction of anaesthesia with 5 mg/kg thiopental, 23 (85%) of 27 patients receiving 1.5 mg/kg succinylcholine, and 18 (56%) of 32 patients receiving 0.5 mg/kg succinylcholine had excellent intubating conditions at 60 s. Naguib et al . [12] also found the incidence of excellent intubating conditions following induction with 2 μ g/kg fentanyl and 2 mg/kg propofol to be 0.0%, 43.3%, 60.0%, 63.3%, 80.0% and 86.7% of patients after 0.0, 0.3, 0.5, 1.0, 1.5, and 2.0 mg/kg succinylcholine, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It minimizes the incidence of idiopathic malignant hyperthermia, myalgia, masseter spasm, rhabdomyolysis, and hemodynamic changes (10). It reduces the aggravated hyperkalemia in end-stage renal failure, burn, and potassium sparing diuretics patients (26).…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the aggravated hyperkalemia in end-stage renal failure, burn, and potassium sparing diuretics patients (26). It avoids the excessive increase in intracranial pressure in head injuries and minimizes the increase in both intra-abdominal and intra-gastric pressures, decreasing the incidences of vomiting and consequent aspiration (10). …”
Section: Discussionmentioning
confidence: 99%